Neka teorijska određenja upravljanja znanjem / Some Theoretical Determination of Knowledge Management - E. Rašidović, Beba (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
Knowledge management in modern times has become an unavoidable concept in an effort to overcome everyday production and distribution of huge amounts of information and new knowledge based on them that which, thanks to the advancement of technology, is becoming increasingly obsolete. The concept, however, is not new, though it was initialized at the end of the 20th and early 21st centuries in an effort to find a new interdisciplinary business model. The main reasons of this actualization lie in globalization, competitiveness, influence on the price of a product on the market, the number of employees and their restructuring and the need for innovations. The paper therefore deals with some theoretical definitions of knowledge management by considering other theoretical traditions that have influenced the development of this concept.